The theoretical and practical aspects of human resource management strategy development: A case of Lithuanian telecommunication sector - Stankevičienė, Asta; Krivka, Algirdas; Liučvaitienė, Aušra (Business: Theory and Practice, 2009)
The human resources are considered as the important factor, which makes a significant impact on the performance of the organization. Therefore, the development of human resource management strategy has become the topical issue in today’s business and academy world. The paper analyses the aspects of human resource management strategy development in telecommunication companies. The research has revealed that the majority of the telecommunication companies understand the necessity of the human resource management strategy. However, the development of human resource management strategy is restricted by the attitudes of high-level managers and behaviour of employees. The companies, which participated in the survey, partly follow the widely accepted strategy development models. On the other hand, the means for the strategy development and implementation are not clear and the strategy does not reflect the main attitudes toward human resource management. The paper presents the strategy development chart which creates the preconditions to tackle the problems indicated in the survey. At the end of the paper the results of the survey are summarized and the conclusions are presented.Article in Lithuanian.Žmogiškųjų išteklių valdymo strategijos rengimo teoriniai ir praktiniai aspektai: Lietuvos telekomunikacijų sektoriaus atvejisSantrauka. Žmogiškieji ištekliai yra laikomi svarbiu veiksniu, turinčiu reikšmingą įtaką organizacijos veiklos rezultatams. Todėl žmogiškųjų išteklių valdymo strategijos rengimas yra aktuali šiandienos verslo ir akademinio pasaulio problema. Straipsnyje analizuojami žmogiškųjų išteklių valdymo strategijos rengimo aspektai telekomunikacijų įmonėse. Tyrimas parodė, kad dauguma telekomunikacijų įmonių suvokia žmogiškųjų išteklių valdymo strategijos būtinybę. Tačiau žmogiškųjų išteklių valdymo strategijos  rengimą  riboja  aukščiausiojo  lygio  valdovų  požiūris  ir  darbuotojų  elgsena.  Įmonės,  dalyvavusios  tyrime,  iš  dalies vadovaujasi plačiai pripažintais strategijos rengimo modeliais. Kita vertus, strategijos rengimo ir įgyvendinimo priemonės nėra aiškios, o strategija neišreiškia pagrindinio požiūrio į žmogiškųjų išteklių valdymą. Straipsnyje pateikiama strategijos rengimo schema,  kuri  sudaro  prielaidas  spręsti  tyrime  nustatytas  problemas.  Straipsnio  pabaigoje  apibendrinami  tyrimo  rezultatai  ir pateikiamos išvados.Reikšminiai  žodžiai:  žmogiškųjų  išteklių  valdymas,  žmogiškųjų  išteklių  valdymo  strategija,  verslo  ir  korporacijos  strategija, rengimas ir įgyvendinimas.First Published Online: 10 Dec 2009